Perancangan Alat Untuk Media Belajar Logika Pemrograman Menggunakan STM32 - Sukry Harly; Riky Febriansyah (Jurnal Cakrawala Akademika, 2024)
Currently, various programming learning media have been developed, one of which is a game-based visual approach (Game Based Learning). This is very influential in fostering the enthusiasm for learning for students and is able to be the initial provision for students in facing this very rapid technological progress. In today's technological developments in education, there are many benefits that can be felt by all levels of society. Along with the increasing need in an increasingly sophisticated world of education, it can make teaching easier to make teaching and learning activities more effective, such as programming logic learning media for elementary school level students. The methods used in this research are observation, interview, literature study, analysis R&D, prototype, and design. The functional objective of this research is to make it easier for students to understand programming logic with learning, practice, and play methods. Saat ini telah banyak dikembangkan berbagai media pembelajaran pemrograman, salah satunya adalah pendekatan visual berbasis permainan (Game Based Learning). Hal ini sangat berpengaruh dalam menumbuhkan semangat belajar bagi siswa dan mampu menjadi bekal awal bagi siswa dalam menghadapi kemajuan teknologi yang sangat pesat ini. Dalam perkembangan teknologi dibidang pendidikan sekarang ini, banyak manfaat yang bisa dirasakan oleh lapisan masyarakat. Seiring dengan naiknya kebutuhan didunia pendidikan yang semakin canggih, dapat memudahkan mengajar agar lebih mengefektifkan kegiatan belajar mengajar seperti halnya media belajar logika pemrograman untuk siswa tingkatan Sekolah Dasar. Metode yang digunakan dalam penelitian ini adalah observasi, wawancara,studi pustaka, analisa R&D, prototype, dan perancangan. Tujuan fungsional dari penelitian ini adalah mempermudah siswa memahami logika pemrograman dengan metode belajar, praktik, dan bermain.